Evaluating Nursing and other Medical Staff Members’ Knowledge of Occupational Safety and Health Risks in A Teaching Hospital - Ismail , Moamen Abdelfadil; Al-Sobhi, Huda Abdul Rahman; Al-Sobhi, Hind Abdul Rahman; Alhazmi, Osama Mohsen H; alahmadi, Abduljalil salah S; Al Sharida , Saad Abdullah Muhammad; Aljohani, Sami Hammad; ALGethami , Amerah Mastour; Alshehri, Fatima Ali; Abdullah , Sarah Mohammed; Alharbi, Ibtihal Saud S; ALRASHEEDI, BJAD ABDULLAH HADHRAM; et al. (Journal of Ecohumanism, 2024)
Background: Healthcare workers, particularly nurses, are exposed to various occupational health and safety risks due to the nature of their work. These risks include physical, chemical, biological, and psychological hazards, which can affect both their well-being and the quality of patient care. Despite the importance of occupational health and safety (OHS) in healthcare settings, there remains a significant gap in the level of awareness among healthcare professionals, especially nurses, regarding these risks. This study aims to assess the level of awareness of OHS hazards among nursing professionals in a teaching hospital and identify areas requiring further education and intervention. Methods: This study was conducted over a three-month period and involved 200 nursing staff from various departments of a teaching hospital. A structured questionnaire consisting of demographic questions and 27 items assessing awareness of different occupational health and safety hazards was distributed. The questionnaire covered general awareness and specific knowledge of physical, chemical, electrical, mechanical, biological hazards, and safety practices. The awareness level was measured on a scale from 1 (Not Aware) to 5 (Fully Aware), with a maximum score of 135. Data were analyzed using descriptive statistics, and the relationship between demographic factors and awareness scores was evaluated. Results: The majority of participants (93.3%) were female, with a mean age of 30.2 years and an average work experience of 7.6 years. The study revealed that 44% of participants had full awareness of general OHS risks, while specific awareness varied across different hazards. Full awareness of physical hazards was demonstrated by 24%–27% of respondents, with 59.4% fully aware of workplace infections and 52.7% recognizing respiratory risks from chemical exposures. A moderate level of awareness was observed in 28%–36% of participants for various hazards, while a small percentage (1%–5%) showed no awareness in these areas. Awareness of occupational safety practices such as PPE use, hand hygiene, and incident reporting was also evaluated, with 55.4% fully aware of PPE’s role in injury prevention and 77.4% knowledgeable about proper hand hygiene practices. Conclusion: The study highlights significant variations in the level of awareness of occupational health and safety risks among nursing professionals in a teaching hospital. While general awareness is relatively high, there are notable gaps in knowledge regarding specific hazards, particularly in relation to chemical, electrical, and mechanical risks. The findings underscore the need for targeted educational programs and interventions to improve awareness and adherence to OHS practices, ultimately enhancing workplace safety and the quality of care delivered to patients